The use and misuse of procalcitonin in the management of pneumonia: a retrospective analysis at a large tertiary care center - Doris C. Obimba; Aaron Shaykevich; Danielle R. Vitale; Christopher A. Rudmann; Heather Korrie; Joseph Miles; Christopher Noel; Ivayla I. Geneva (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract